Pengaruh Sarapan Pagi Bagi Mahasiswa PGMI Saat Menghadapi Pelajaran terhadap Kondisi Tubuh dan Mental - Shellatul Muhibbah; Wiranda Anggela; Nur Alfi Husna; Musripa Ulwani; Devi Wulansari (Yayasan Literasi Sains Indonesia, 2024)
This study aims to analyze the influence of breakfast on the physical and mental condition of PGMI students when facing learning. The method used was a quantitative survey involving 20 PGMI students. Data was collectad through a questionnaire designed to measure the frequency of measure the frequency of breakfast, the type of food consuned in the morning, as well as the physical and mental condition of PGMI students. Data analysis was carried out using descriptive statistics and dlinear regression to determine the relationship between breakfast and academic performance. The analysis uses descriptive statistics and linear regression to explain the relationship between breakfast habits and academic performance. Findings suggest that regular breakfast consumption is associated with improved energy levels, concentration, mood, and overall health among college student, highlighting the need to promote healty breakfast practices in academic settings. This research investigates the impact of breakfast habits on the physical and mental condition og PGMI students. Using a quantitative survey mothodology involving 20 students, this research collected data regarding the frequency of breakfast, the type of food consumed, and its effect on energy, concentration, as well as better moods compared to those who did not eat breakfast. These findings emphasize the importance of a nutritious breakfast in supporting students’ physical and mental healt, and have implications for their academic performance.